2018
DOI: 10.1016/j.cryobiol.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of superoxide ion formation in hypothermia/rewarming induced contractile dysfunction in cardiomyocytes

Abstract: Rewarming following accidental hypothermia is associated with circulatory collapse due primarily to impaired cardiac contractile (systolic) function. Previously, we found that reduced myofilament Ca sensitivity underlies hypothermia/rewarming (H/R)-induced cardiac contractile dysfunction. This reduced Ca sensitivity is associated with troponin I (cTnI) phosphorylation. We hypothesize that H/R induces reactive oxygen species (ROS) formation in cardiomyocytes, which leads to cTnI phosphorylation and reduced myof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Thus, it does not appear that the decrease in contractility of cardiac myocytes (heart failure) after rewarming can be solely attributed to dysregulation of [Ca 2+ ] cyt release and reuptake. By the use of isolated, electrically stimulated myocytes cooled to 15°C, and rewarmed we have documented that the reduction in force generation, independent of [Ca 2+ ] cyt levels, is the effect of an increased phosphorylation of cardiac troponin I (cTnI) leading to reduced Ca 2+ sensitivity of the contractile response after rewarming ( Han et al, 2010 ; Schaible et al, 2016 , 2018 ). Further, with relevance to the group (CPBc) treated with a chemical cardioplegic solution during HCA in the present study; we observed both maintained cytosolic Ca 2+ levels and myofilament Ca 2+ sensitivity in myocytes, which were not electrically stimulated (cardioplegic) during cooling to 15°C and rewarming ( Han et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it does not appear that the decrease in contractility of cardiac myocytes (heart failure) after rewarming can be solely attributed to dysregulation of [Ca 2+ ] cyt release and reuptake. By the use of isolated, electrically stimulated myocytes cooled to 15°C, and rewarmed we have documented that the reduction in force generation, independent of [Ca 2+ ] cyt levels, is the effect of an increased phosphorylation of cardiac troponin I (cTnI) leading to reduced Ca 2+ sensitivity of the contractile response after rewarming ( Han et al, 2010 ; Schaible et al, 2016 , 2018 ). Further, with relevance to the group (CPBc) treated with a chemical cardioplegic solution during HCA in the present study; we observed both maintained cytosolic Ca 2+ levels and myofilament Ca 2+ sensitivity in myocytes, which were not electrically stimulated (cardioplegic) during cooling to 15°C and rewarming ( Han et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously documented hypothermia-rewarming induced cardiac dysfunction in both in vivo and in vitro models 23 28 . Underlying pathophysiologic mechanisms include derangement in metabolism and calcium homeostasis 23 25 , 29 , elevated protein kinase A levels with increased phosphorylation in myocardial contractile proteins 27 , 28 , 30 , and reactive oxygen species formation 31 . Likewise, after rewarming, we have documented derangements in renal 32 and nervous tissue morphology 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously have documented hypothermia-rewarming induced cardiac dysfunction in both in vivo and in vitro models [20,[27][28][29][30][31]. Underlying pathophysiologic mechanisms include derangement in metabolism and calcium homeostasis [20,27,28,32], elevated protein kinase A levels with increased phosphorylation in myocardial contractile proteins [30,31,33], and reactive oxygen species formation [34]. Likewise, after rewarming, we have documented derangements in renal [35] and nervous tissue morphology [36].…”
Section: Resuscitation During Hypothermia and Normothermiamentioning
confidence: 95%